Troublesome words - Bryson, Bill. (London : Penguin Books, 2009)
More than one thousand alphabetically arranged entries define and explain a variety of difficult words from the English language.
Original title: The Penguin dictionary of troublesome words.
Includes bibliographical references.
Adult.
Adult
Keywords: English language -- Usage -- Dictionaries; English language -- Usage -- Dictionaries